2023
DOI: 10.1093/jb/mvad053
|View full text |Cite
|
Sign up to set email alerts
|

Trans-scale thermal signaling in biological systems

Abstract: Summary Biochemical reactions in cells serve as the endogenous source of heat, maintaining a constant body temperature. This process requires proper control; otherwise, serious consequences can arise due to the unwanted but unavoidable responses of biological systems to heat. This review aims to present a range of responses to heat in biological systems across various spatial scales. We begin by examining the impaired thermogenesis of malignant hyperthermia in model mice and skeletal muscle cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…It was found that temperature fluctuations can be observed even within single cells. 26 This process has led to the concept of "thermal signaling," which is the process by which heat is released through intracellular biochemical reactions and influences cellular functions across different spatial scales, from molecules to individual organisms. 26 It involves releasing heat through various biological processes and biomolecules, such as ATP/ GTP hydrolysis and biopolymer complex formation and disassembly.…”
Section: Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…It was found that temperature fluctuations can be observed even within single cells. 26 This process has led to the concept of "thermal signaling," which is the process by which heat is released through intracellular biochemical reactions and influences cellular functions across different spatial scales, from molecules to individual organisms. 26 It involves releasing heat through various biological processes and biomolecules, such as ATP/ GTP hydrolysis and biopolymer complex formation and disassembly.…”
Section: Temperaturementioning
confidence: 99%
“…Also, lower local energy fluctuation can affect cellular function, as energy is exchanged with biomolecules in many intracellular reactions. It was found that temperature fluctuations can be observed even within single cells . This process has led to the concept of “thermal signaling,” which is the process by which heat is released through intracellular biochemical reactions and influences cellular functions across different spatial scales, from molecules to individual organisms .…”
Section: Key Factors In Biochemistrymentioning
confidence: 99%
“…The information from the sensors is transmitted into the cell via various types of signaling modes, such as Ca 2+ and phosphorylation. Heat itself can also be a signaling, i.e., the thermal signaling [1][2][3]. Cellular responses are transduced and coordinated at the organismal level to determine behavior.…”
mentioning
confidence: 99%